Lilliput - Gayton, Sam (London Andersen Press, 2013)
Inspired by Gulliver's Travels, Lilliput is an exhilarating and imaginative adventure filled with cunning escape plans, evil clock makers, and talkative parrots. Join Lily as she travels through eighteenth-century London over rooftops, down chimneys, and into chocolate shops-on a journey to find the one place in the world where she belongs home.
Keywords: Rescues -- England--London -- Apprentices